CORPORATE SOCIAL RESPONSIBILITY: ACTUALIZATION OF VALUE OF JAUDATUL ADAA (WELL ENDING) IN ISLAMIC BANKING - Mais, Rimi Gusliana (The International Journal of Accounting and Business Society, 2017)
CSR is a must for all companies including sharia banking as regulated in legislation. so that today all banks do CSR reporting as a means of publication widely. Unfortunately, the values contained in current CSR reporting contain only secular activities, while Indonesia is a country with 200 million Muslims who are entitled to use Islamic religious values in their lives that are included in economic activities, including CSR. This study aims to find the appropriate Islamic values and can be applied in CSR activities. This research uses qualitative methods using an Islamic perspective as a worldview. This study found one value in Islam that can be a reference company, a sharia bank, namely the value of Jaudatul ’Ada (Well Ending).  Jaudatul ’Ada can be a differentiator of csr activities conducted Islamic banking with conventional banking because Jaudatul ’Ada is part of the value Ihsan (goodness/virtue) is a spiritual value linking well ending more comprehensive and there is not a dichotomy between material (the world) and the spiritual (hereafter). By using Jaudatul ’Ada value, CSR performed by syaria bank is not only pursuing sustainability business but further pursuing the sustainability of maslahah (great benefit).Keyword: CSR, Islamic Value, economic, Jaudatul ‘Ada